Implementation of Facilities and Infrastructure Standards in Supporting the Learning Process at MTs Al-Fathimiyah - Fairuz Sausan Kamil; Arya Wiradarma Saputra; Azzahra Arrohma; Fitria Nursani Rofifah Supriyadi; Hinggil Permana (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
This study looks into how standards for facilities and infrastructure are used to help learning at MTs Al Fathimiyah. The basis for this research is the important part that good educational facilities play in creating a positive learning atmosphere, boosting student enthusiasm, and supporting teachers in teaching well. The aim of this research is to examine the state, use, and difficulties of the school's facilities, along with the methods used to tackle the current issues. The study uses a descriptive qualitative approach, gathering detailed information through direct observations and interviews with the school staff. The results show that MTs Al Fathimiyah has effectively offered adequate facilities like classrooms, labs, libraries, and digital resources such as projectors, smart TVs, and computers, which greatly aid teaching and learning. Nonetheless, there are still challenges, especially in obtaining textbooks when the curriculum changes and the absence of facilities for students with special needs. To address these issues, the school employs inventive strategies, which include enhancing teacher creativity, partnering with outside organizations, and making use of BOS funds. The outcomes of this research emphasize the need for ongoing facility development, inclusive education, and updating to meet digital learning requirements. Additionally, cooperation among schools, the government, and outside partners is essential to improve infrastructure and ensure the ongoing delivery of quality education.